2014
DOI: 10.1186/s12917-014-0175-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypercobalaminaemia is associated with hepatic and neoplastic disease in cats: a cross sectional study

Abstract: BackgroundWhen increased serum cobalamin concentrations are encountered clinically they are usually attributed to parenteral supplementation, dietary factors, or otherwise ignored. However, recently, hypercobalaminaemia has been associated with numerous diseases in humans, most notably neoplastic and hepatic disorders. The aim of this retrospective, observational, cross-sectional study was to determine the significance of increased cobalamin in cats.ResultsIn total, 237 records were retrieved and 174 cats, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
2
28
1
3
Order By: Relevance
“…These hypercobalaminemic dogs had mostly (73%) signs of chronic GI disease, and a neoplastic condition could not be definitively excluded in 82% of the dogs. These findings suggest that hypercobalaminemia is less frequently observed in dogs than in cats, in which a prevalence of 14% (28 of 202 cats) was observed in the study above (unpublished data), and that hypercobalaminemia might be of clinical relevance in dogs that have not received supplemental cobalamin. A higher prevalence (36%) of hypercobalaminemia is reported (Bertolani C, Tabar MD, Esparza A, et al Hypercobalaminemia in 144 samples from cats and dogs.…”
Section: Laboratory Testing To Evaluate Cobalamin Statusmentioning
confidence: 64%
See 1 more Smart Citation
“…These hypercobalaminemic dogs had mostly (73%) signs of chronic GI disease, and a neoplastic condition could not be definitively excluded in 82% of the dogs. These findings suggest that hypercobalaminemia is less frequently observed in dogs than in cats, in which a prevalence of 14% (28 of 202 cats) was observed in the study above (unpublished data), and that hypercobalaminemia might be of clinical relevance in dogs that have not received supplemental cobalamin. A higher prevalence (36%) of hypercobalaminemia is reported (Bertolani C, Tabar MD, Esparza A, et al Hypercobalaminemia in 144 samples from cats and dogs.…”
Section: Laboratory Testing To Evaluate Cobalamin Statusmentioning
confidence: 64%
“…However, recent data in people suggest that hypercobalaminemia is an underestimated finding that can reflect a number of serious underlying diseases such as solid neoplasms, hematological and other malignancies, and hepatic or renal diseases . Abnormally high serum cobalamin concentrations occur in cats with hepatic and neoplastic diseases . A retrospective analysis of the medical records and data from 592 dogs that were presented for further diagnostic workup at the University of Leipzig Small Animal Clinic showed that 2% (n = 11) of all dogs in which serum cobalamin status was determined and that did not receive any supplemental cobalamin (n=487 dogs) had a serum cobalamin concentration above RI, ranging from 1,100‐3,561 ng/L (median: 1,334 ng/L) (unpublished data).…”
Section: Laboratory Testing To Evaluate Cobalamin Statusmentioning
confidence: 99%
“…Im Zuge der Anorexie findet sich mitunter eine prärenale Azotämie (Dehydratation). Häufig ist auch der Serum-Cobalamin-Spiegel (Vitamin B 12 ) suboptimal, aber auch eine Hypercobalaminämie ist möglich [6]. Da Cholangitiden bei der Katze auch mit einer Pankreatitis, einer IBD oder beiden (feline Triaditis) auftreten können, empfiehlt sich weiterhin die Bestimmung der felinen spezifischen Pankreaslipase (Spec fPL) sowie des Folsäure-(Vitamin B 9 ) und Cobalamin-Spiegels (Vitamin B 12 ) im Serum.…”
Section: Lymphozytäre Cholangitisunclassified
“…Of these, 237 records were identified after the database search, and 174 cases met the eligibility criteria.85 …”
Section: Participants: 13(a) Report the Numbers Of Owners/managersmentioning
confidence: 99%
“…A record of prior cobalamin supplementation (within the three months before presentation) was identified in 18 cases (16 with serum cobalamin greater than the reference interval, 1 with cobalamin within the reference interval and 1 with cobalamin below the reference interval).85 …”
Section: (B) Give Reasons For Nonparticipation At Each Stage and Atmentioning
confidence: 99%